HUBUNGAN KREATIVITAS MAHASISWA DENGAN HASIL BELAJAR MATA KULIAH MANAJEMEN USAHA BOGA (MUB) PADA PROGRAM STUDI TATA BOGA JURUSAN KESEJAHTERAAN KELUARGA FT UNP - Rahmaneli, Seprina; Silfeni, Silfeni; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
Depends on the observation and interview with the students of cookery family welfare department, showed that student creativity with the low achievement. The goal of this research is to reveal students creativity with the achievement for cookery management in cookery study program of family welfare department technic faculty of UNP. This research describe 1) students creativity for cookery management in cookery study program, 2) the student achievement for for cookery management in cookery study program, 3) the correlation between Students Creativity with the study result of Cookery Management in Coockery Study Programme. The kind of this research is descriptive research with correlation approach. The population of this research is the students of cookery management which are 102 people consist of 31 people for restaurant cookery management, 36 people for catering cookery management and 31 people for industrial cookery management. The sampling technic is total sampling. The kind of the instrument is questionare that arranged in Likert scale through validity and realibility test. Data analysis technic is descriptive statistic and correlation with product moment correlation formula then processed by using SPSS 15.0 version. The result shows that 40,2% students creativity is in the middle chategory, 46,1% students didn’t pass the cookery management. There is positive and significan correlation between students creativity (X) with students achievement for cookery management (Y), with the correlation number 0,835 whereas tcounted > ttable (15,168 > 1,658). The student creativity variable (X) give 69,7% contribution for the student achievement in cookery management with 30,3% other variable. These results indicate that there is a relationship with the student learning outcomes creative course MUB The existence of student creativity will provide a positive impact on learning outcomes.